Heterologous Booster Profiles for Recipeints of CoronaVac Inactivated Primary Vaccine: A Scoping Review - Handayani, Ety Sari; Hidayah, Nurul (Universitas Padjadjaran, 2023)
The administration of booster vaccines has been implemented in a number of countries. Unfortunately, there are limited studies of the immune response after booster to recipient with CoronaVac inactivated primary vaccine. This scoping review aims to determine heterologous booster profiles for recipients of the CoronaVac inactivated primary vaccine. This study obtained data from PubMed, Cochrane Library, Medrxiv, Google Scholar and Grey literature. The inclusion criteria were Sars-Cov-2 article, heterologous boosters and CoronaVac vaccine published from 2020 to 2022, written in English, and in a form of an original research articles, project reports, articles with RCT research designs, cohorts and articles with human research subjects. The keywords were Sars-cov-2, COVID-19, heterologous boosters and CoronaVac. Profiles assessed were heterologous vaccine types, immune responses, intervals between the booster administration and the primary vaccine, and heterologous booster doses. The number of articles that met the inclusion criteria was 19 articles. Types of vaccines that could be used as heterologous boosters for recipients of CoronaVac inactivated primary vaccine were BNT162b2, AZD1222, mRNA-1273, Ad26.COV2-S. The administration of heterologous booster vaccines for recipients of the CoronaVac inactivated primary vaccine was able to increase antibody levels against of the Sars-Cov-2 variants of Mild, Beta, Gamma, Delta and Omicron. The doses of booster vaccines (Ad26.COV2-S, BNT162b2, AZD1222, mRNA-1273 (Moderna) and CoronaVac) for the CoronaVac recipients respectively were 0.5 mL, 0.3 mL, 0.5mL, 100 µg and 0.5 mL. In conclusion, the heterologous boosters for the CoronaVac recipients could enhance immune responses against the Sars Cov 2.